Determination of low molecular weight volatiles in Ficus carica using HS-SPME and GC/FID - Oliveira, A.P. (2011)
Ficus carica L. is one of the earliest cultivated fruit trees, having an important consumption in Mediterranean countries. In this work, the volatile compound profiles of two characteristic Portuguese white varieties (‘‘Pingo de Mel” and ‘‘Branca Tradicional”) was determined by HS-SPME and GC/FID. Leaves, pulps and peels, submitted to freezing and lyophilisation treatments, were analysed. The two varieties presented a similar profile composed of eight volatile compounds: acetaldehyde, ethyl acetate, methanol, ethanol, hexanal, limonene, (E)-2-hexenal and octanal. The total volatile content was different among the vegetal materials, following the order leaves > peels > pulps. Methanol and ethanol are the major compounds in all samples. The developed procedure revealed to be rapid, sensitive, reproducible and accurate. The detection limit values were low, and the method precise. The recovery values for acetaldehyde, ethyl acetate, methanol and ethanol were generally high, suggesting that it will be most suitable for compounds with low molecular weight. Due to its rapidity and low cost, this technique can be useful in the quality control of fig fruit and leaves.